Waste Composting as an Effort to Realize Kelusa, Payangan, Gianyar-Bali Village as an Ecotourism Village - Muliarta I Nengah; Sukmadewi Desak Ketut Tristiana; Pratama Gede Agus Surya (Asian Journal of Community Services, 2023)
Community service carried out in Kelusa Village, Payangan, Gianyar, Bali aims to help the community in improving knowledge and skills in waste management. Village waste management is important to realize Kelusa Village as an ecotourism village. The methods used are observation, interviews, counseling, and plot demonstrations. Based on the results of interviews with 18 participants in composting training and demonstration plots, it was found that the villagers were not used to sorting garbage because they were lazy and did not have time. The residents of Kelusa Village have also never done composting because they don't know how to compost. After the training, the villagers wanted to make compost, because they already knew the method of composting.